Stability Analysis for a Flywheel Supported on Magnetic Bearings with Delayed Feedback Control - Ling L. Zhang; Jian H. Huang (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the model of the rotor dynamics of the flywheel is given using a rigid rotor supported on magnetic bearings. The phase lag of the control loop is modeled by a simple time delay. Limits of stability and the associated vibration frequencies are described in terms of nondimensional magnetic bearing stiffness and damping and nondimensional parameters of flywheel speed and time delay. Compared to the theoretical values, the simulation results and experimental measurements show the stability boundaries of the PD controller have the same qualitative tendencies.